Conservation Genomic Analysis of the Croatian Indigenous Black Slavonian and Turopolje Pig Breeds - Lukić, Boris; Ferenčaković, Maja; Šalamon, Dragica; Čačić, Mato; Orehovački, Vesna; Iacolina, Laura; Curik, Ino; Cubric-Curik, Vlatka (Frontiers in Genetics, 2020)
The majority of the nearly 400 existing local pig breeds are adapted to specific environments and human needs. The demand for large production quantities and the industrialized pig production have caused a rapid decline of many local pig breeds in recent decades. Black Slavonian pig and Turopolje pig, the latter highly threatened, are the two Croatian local indigenous breeds typically grown in extensive or semi-intensive systems. In order to guide a long-term breeding program to prevent the disappearance of these breeds, we analyzed their genetic diversity, inbreeding level and relationship with other local breeds across the world, as well as modern breeds and several wild populations, using high throughput genomic data obtained using the Illumina Infinium PorcineSNP60 v2 BeadChip. Multidimensional scaling analysis positioned Black Slavonian pigs close to the UK/North American breeds, while the Turopolje pig clustered within the Mediterranean breeds. Turopolje pig showed a very high inbreeding level (FROH>4Mb = 0.400 and FROH>8Mb = 0.332) that considerably exceeded the level of full-sib mating, while Black Slavonian pig showed much lower inbreeding (FROH>4Mb = 0.098 and FROH>8Mb = 0.074), indicating a planned mating strategy. In Croatian local breeds we identified several genome regions showing adaptive selection signals that were not present in commercial breeds. The results obtained in this study reflect the current genetic status and breeding management of the two Croatian indigenous local breeds. Given the small populations of both breeds, a controlled management activity has been implemented in Black Slavonian pigs since their commercial value has been recognized. In contrast, the extremely high inbreeding level observed in Turopolje pig argues for an urgent conservation plan with a long-term, diversity-oriented breeding program.